Analysis of Rio de Janeiro city budget with focus on tax collection (Research, Society and Development, 2022)
This article aims to present a vision about the main sources of financial resources for public entities and, at the same time, serves as an instrument for reflection about the real benefits that events, periodic and non-periodic, can bring to the state, also serving as a counterpoint to the demonstrations that occurred in Brazil about the population point of view, at that moment, against to the World Cup in the country. The foundation was entirely made using the National Tax Code as a support. Its main points were compiled and presented for a better understanding of the tax structure in Brazil and its applications. In the same way, comments were made about the main current taxes in Rio de Janeiro city and their practical applications, showing in which ways these are the main sources of public revenue and how this revenue may be reverted for the benefit of the population itself. News and articles served as a basis for a better understanding of the behavior of tourism in Brazil and in Rio de Janeiro, and revealed through relevant data how these events move people and the national and regional economy as a whole.  Finally, after the treatment of these data and their transformation into graphics, it became clear how these events bring profitability and visibility to Rio de Janeiro, leading to the conclusion that investing in tourism is in fact a good strategy to be maintained.